THE ROLE OF TEACHER PROFESSIONALISM AND CONTINUOUS PROFESSIONAL DEVELOPMENT ON THE QUALITY OF EDUCATION AND ITS IMPLICATIONS ON THE QUALITY OF ELEMENTARY SCHOOL TEACHERS IN PULOSARI DISTRICT, PANDEGLANG REGENCY - Nuroniah, Enung; Rustandi, Tata; Permana, Angrian (Yayasan Education and Social Center, 2025)
In recent years, attention to the quality of education has increased significantly. As policymakers and stakeholders recognize the essential role of education in driving social and economic development, ensuring that students acquire relevant knowledge and skills for their future success has become a critical concern. This study was conducted at public elementary schools (SDN) in Pulosari District, Pandeglang Regency, aiming to examine the influence of teacher professionalism and the implementation of continuous professional development (CPD) on educational quality, as well as its impact on teacher quality. The research employed descriptive analysis based on index scores, while Structural Equation Modeling with Partial Least Squares (SEM-PLS) was used for inferential analysis. The SEM-PLS analysis included evaluation of the outer and inner models, followed by testing seven formulated hypotheses. The study involved 144 teachers across seven SDN in Pulosari, with sample selection determined proportionally. The findings reveal that five hypotheses were supported, while two were not. Teacher professionalism demonstrated a significant impact on both teacher quality and educational outcomes. In contrast, continuous professional development did not show a direct significant effect on educational quality, although it did positively influence teacher quality. Furthermore, teacher quality was found to significantly affect educational quality. Among the two mediation hypotheses, only one was accepted: the mediating role of teacher quality between teacher professionalism and educational quality. The mediating effect of teacher quality in the relationship between CPD and educational quality was not supported. In conclusion, both teacher professionalism and CPD serve as important indicators of educational quality. However, CPD cannot be considered a direct predictor of improvements in educational outcomes.